Diskusi Kelompok Menjawab Tantangan Pengelolaan Museum dalam Perspektif Museum Modern Bersama Badan Keahlian DPR RI - Puspasari, Shinta; Adesta , Erry Juilan T.; Alie, Marzuki (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
Traditional museums need to transform into modern museums to optimize their tasks and functions not only for educational purposes but also for tourism. The problems faced by museums in Indonesia today need to be discussed to find solutions that answer the challenges of museum management from a modern museum perspective. The DPR RI expert body as a partner in collaboration with Universitas Indo Global Mandiri initiated and facilitated group discussions by inviting various museum managers in Palembang. The discussion began with the presentation of material related to the problems and challenges faced by museums in the digital era and continued with a discussion session. The results of the group discussion activities concluded that it is imperative for museums to transform into modern museums by adopting digital technology to answer museum problems and challenges by optimizing the management of collections, human resources, facilities, and museum services through the use of Information and Communication Technology (ICT). The challenge of presenting museums as educational and tourist destinations is expected to be answered by presenting digital technology-based innovations that will make museum collections seem alive, presenting imagination for visitors so that they can better understand the historical and cultural values ​​​​of museum collections in Indonesia. === Museum tradisional perlu bertansformasi menjadi museum modern untuk mengoptimalkan tugas dan fungsi nya tidak hanya untuk tujuan edukasi juga wisata. Permasalahan yang dihadapi museum di Indonesia saat ini perlu didiskusikan untuk mencari solusi yang menjawab tantangan pengelolaan museum dalam perspektif museum modern. Badan keahlian DPR RI sebagai mitra bekerjasama dengan Universitas Indo Global Mandiri menginisiasi dan memfasilitas diskusi kelompok dengan mengundang berbagai pengelola museum di Palembang. Diskusi diawali dengan pemaparan materi terkait permasalahan dan tantangan yang dihadapi museum di era digital dan dilanjutkan dengan sesi diskusi. Hasil kegiatan diskusi kelompok disimpulkan bahwa mutlak bagi museum untuk bertransformasi menjadi museum modern dengan mengadopsi teknologi digital untuk menjawab permasalahan dan tantangan museum dengan mengoptimalisasi pengelolaan koleksi, SDM, fasilitas, dan layanan museum lewat pemanfaatan Teknologi Informasi dan Komunikasi (TIK). Tantangan untuk menghadirkan museum sebagai tujuan edukasi sekaligus wisata diharapkan dapat terjawab dengan menghadirkan inovasi berbasis teknologi digital yang akan membuat koleksi museum menjadi seakan hidup menghadirkan imajinasi bagi pengunjung sehingga dapat lebih memaknai nilai sejarah dan budaya yang dimiliki oleh koleksi museum di Indonesia.